Phylogenetic Analysis Of Bacilli From Haloalkaline Lonar Soda Crater - VISHAL R. DHUNDALE,; VIJAYSHREE M. HEMKE, (International Journal of Pharma and Bio Sciences, 2015)
In the last decade, special attention has been given to the investigation of the microbial communities in soda lakes using traditional isolation methods and molecular biology techniques. Aerobic, haloalkaliphilic bacteria were isolated and characterized from sediment and water samples collected from Lonar Soda Lake. The uniqueness of the Lonar Lake water is its salinity and alkalinity. Culture dependent phenotypic characterization and 16S rRNA based phylogenetic analysis were applied. One hundred and fourteen bacterial strains were isolated using different enrichment media. Out of One hundred and fourteen, twenty nine bacilli strain were selected for 16S rRNA sequencing. The phylogenetic position indicated the Lonar lake bacterial strains were related to phylum Firmicutes and belongs to three genera Bacillus, Lysinibacillus, Oceanobacillus. Most of the isolates produced biotechnologically important amylase, lipase and protease enzymes at alkaline pH. Bacillus cereus, Bacillus pseudofirmus and Bacillus flexus, Bacillus sp. were found multienzyme producer. Lonar Lake harbors a wealth of diverse microorganisms with useful commercial properties. Thus, the culture-dependent approach used in the present study contributes to our understanding of Lonar lake bacilli diversity and provides useful information on many fascinating cultures in this extreme environment.